Bully be gone: What is workplace bullying and why does it matter? - Curry, Lynne (Institutional Knowledge at Singapore Management University, 2018)
We have all met at least one in the course of our careers. He, or she, is the angry, aggressive bully who insults you to your face and behind your back. You would expect that at some point they would tire of this behaviour, but bullies thrive on demeaning and belittling you. Meanwhile, being bullied saps your emotional and physical energy until you fi nally resign from a job you once loved.